2010
DOI: 10.5194/os-6-143-2010
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of an Agulhas eddy near the continental slope

Abstract: Abstract. The transformation of Agulhas eddies near the continental slope of southern Africa and their subsequent self-propagation are analyzed in both observational data and numerical simulations. Self-propagation results from a net dipole moment of a generalized heton structure consisting of a surface-intensified anticyclonic eddy and deep cyclonic pattern. Such Agulhas vortical structures can form near the retroflection region and further north along the western coast of southern Africa. We analyze nonlinea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…A first question arises from observations by Lutjeharms (1991) and Duncombe Rae et al (1992) of a ring drifting near the shelf edge in 1989, that entrained cold water from the coastal upwelling system. Similar observations of rings encountering the continental slope were recently analyzed by Baker-Yeboah et al (2010). The frequency of this phenomenon is largely unknown, yet it could be an important contribution to exchanges between coastal and deep-sea waters.…”
Section: J) Agulhas Rings Of the Northern Route And The Continental Ssupporting
confidence: 71%
“…A first question arises from observations by Lutjeharms (1991) and Duncombe Rae et al (1992) of a ring drifting near the shelf edge in 1989, that entrained cold water from the coastal upwelling system. Similar observations of rings encountering the continental slope were recently analyzed by Baker-Yeboah et al (2010). The frequency of this phenomenon is largely unknown, yet it could be an important contribution to exchanges between coastal and deep-sea waters.…”
Section: J) Agulhas Rings Of the Northern Route And The Continental Ssupporting
confidence: 71%
“…In the Benguela upwelling regime, the eddy–slope interaction provides a dynamic link between the slope waters, shelf waters and open ocean. The bathymetry and experimental results for a steep slope-shelf are shown in Figures 16 and 17 (Baker-Yeboah et al, 2010), and those for a mild slope-shelf are shown in Figure 18.
Figure 16.Along-track section of continental bathymetry with a narrow continental slope connected to a broad shelf region off Cape Town, South Africa.
Figure 17.Upwelling on the shelf and deep-ocean eddies along the continental slope of South Africa during July 23 2003 in AVISO SSH shown in an abnormal map.
…”
Section: Internal Waves On a Submerged Topographymentioning
confidence: 99%
“…As illustrated in previous studies, such filaments can extend well in to the thermocline and can 12 360 365 370 375 380 385 be related to dipole dynamics (de Steur et al, 2004;Baker-Yeboah et al, 2010). Such wide intrusions are defined as intense north-northwestward current affecting directly the upper 1500 m and indirectly through the whole water column.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 84%